Guns, germs and steel : the fates of human societies - Diamond, Jared
In the Prologue : Yali's Question..."Why is it that you white people developed so much cargo and brought it to New Guinea, but we black people had little cargo of our own? (p. 14). "This book, written twenty five years later, attempts to answer Yali." (p. 15)...